IbM PADA KELOMPOK KADER ‘AISYIYAH RANTING TANJUNG TENTANG PEMANFAATAN HERBAL YANG AMAN DIKONSUMSI UNTUK KESEHATAN GIGI DAN MULUT PADA IBU HAMIL - Muflihah, Ima Syamrotul; Margiana, Wulan (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2019)
Oral and dental health is one of the things that needs to be considered during pregnancy, this is because pregnant women are one group that is susceptible to dental and oral diseases. During pregnancy natural changes occur in pregnant women, both physiologically, anatomically and hormonally. The influence of these hormonal changes can affect almost all organ systems including the oral cavity. When there are complaints of teeth and mouth during pregnancy, pregnant women are encouraged to immediately go to a dental health facility. But in an emergency to cope with tooth pain, the use of herbal medicines can be given before being referred to a dental clinic or dentist because every health care worker in collaboration with the community can play an important role in encouraging prospective pregnant women to know the condition of their teeth and mouth. In addition, it also increases the awareness of prospective mothers about the importance of oral health and rectifies misunderstandings such as the belief that tooth loss and bleeding in the mouth are normal during pregnancy. The implementation of community service was carried out for cadres ‘Aisyiyah Tanjung Branch where the results of the preliminary study found that the majority of community behavior related to maintaining dental and oral health during pregnancy carried out by pregnant women was still low. Therefore, the team was interested in carrying out community service about the use of herbs for oral and dental health for pregnant women as an alternative solution in increasing the knowledge, attitudes, skills of prospective mothers about oral and dental health, especially during pregnancy to reduce morbidity in pregnant mother. Keywords : Herbs, Teeth and Mouth